Controlled growth of silicon nanocrystallites in silicon oxide matrix using 150 MeV Ag ion irradiation - Chaudhari, P. S.; Bhave, T. M.; Pasricha, R.; Singh, F.; Kanjilal, D.; Bhoraskar, S. V. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2005)
We report the synthesis of silicon nanocrystals grown in silicon oxide matrix by swift heavy ion irradiation. Thin films of silicon oxide (SiO(x)) are irradiated with 150 MeV silver ions at fluence varying from 5 x 10(11) to 1 x 10(13) ions/cm(2). The variation in the properties of silicon nanocrystals embedded in silicon oxide with varying fluence is studied. The energy of the photoluminescence peak corresponding to the silicon nanocrystals is found to be red shifted with increasing fluence. The trends in the broadening of the X-ray diffraction peak with decreasing fluence supports the controlled growth of silicon nanocrystals in silicon oxide matrix. The crystallite size of nanoclusters of silicon is seen to increase with increasing fluence. The results are discussed in view of the structural transformation, in SiO(x) matrix, caused by swift heavy ion irradiation. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: oxide matrix; silicon nanocrystallites; swift heavy ion irradiation

Oriented growth of nanocrystalline gamma ferric oxide in electrophoretically deposited films - Bhave, T. M.; Balasubramanian, C.; Nagar, H.; Kulkarni, S.; Pasricha, R.; Bakare, P. P.; Date, Sadgopal K.; Bhoraskar, S. V. (Hyperfine Interactions, 2005)
Films of nanocrystalline gamma-Fe2O3 were deposited on silicon substrates by using the technique of electrophoretic deposition. The precursor powder was nanocrystalline gamma-Fe2O3, which was synthesized, using DC arc plasma in the oxygen ambient by vapour-vapour interaction in gas phase condensation; at a stabilized arc current of 40 A. This powder was characterized by X-ray diffraction, Transmission Electron Microscopy, Vibrating Sample Magnetometer and Mossbauer Spectroscopy. An increase in directional coercivity was observed in case of films deposited on silicon substrates, which is dramatically significant. Preferred orientation of almost similar sized nanocrystalline magnetic domains in deposited films is evident from the results of X-ray diffraction and Transmission Electron Microscopy results. The preferred alignment of the nanocrystallites seems to be responsible for the significant changes observed in magnetic properties of films.
International Workshop on Nanomaterials, Magnetic Ions and Magnetic Semiconductors Studies mostly by Hyperfine Interactions, M S Univ Baroda, Phys Dept, Baroda, INDIA, FEB 10-14, 2004

Simple oxalate precursor route for the preparation of barium-strontium titanate: Ba1-xSrxTiO3 powders - Khollam, Y. B.; Deshpande, S. B.; Potdar, H. S.; Bhoraskar, S. V.; Sainkar, S. R.; Date, Sadgopal K. (Materials Characterization, 2005)
A simple one-step cation-exchange reaction between the stoichiometric solutions of ammonium titanyl oxalate (ATO) and barium hydroxide+strontium nitrate at room temperature (RT) is investigated successfully for the quantitative precipitation of barium-strontium titanyl oxalate (BSTO): Ba1-xSrxTiO(C2O4)(2).4H(2)O (x=0.25) precursor powders with nearly theoretical yield (greater than or equal to99%). The pyrolysis of BSTO at 730degreesC/4 h in air produced barium-strontium titanate (Ba1-xSrxTiO3; BST) powders. The characterization studies on BSTO and BST powders by using various physico-chemical techniques: micro- and chemical analysis, differential thermal analysis (DTA)/thermo-gavimetric analysis (TGA), XRD, FTIR, X-ray fluorescence (XRF) and scanning electron microscopy (SEM) revealed that the powders formed are cubic, highly pure, stoichiometric and sub-micron-sized with nearly uniform size and shape distribution. The ceramic compacts obtained by sintering the BST pellets at 1300degreesC/4 It showed density similar to95%, dielectric constant epsilon(Tc)similar to9500, tan delta-0.15% and T(C)similar to32 degreesC. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; permittivity; XRF

Effect of a focusing electric field on the formation of arc generated carbon nanotubes - Karmakar, Soumen; Nagar, Harshada; Pasricha, R.; Seth, T.; Sathe, V. G.; Bhoraskar, S. V.; Das, A. K. (Nanotechnology, 2006)
The effect of a focusing electric field on the formation of carbon nanotubes in a direct current arc-plasma is investigated. The hard deposits on the surface of the cathode are the main products, rich in multi-walled carbon nanotubes. It is seen that the focusing electric field has a distinct influence on the yield, purity and morphology of the nanotubes. The yield of the carbon nanotubes under the `focused field condition' has been found to be higher than that derived from the normal electrode configuration. It has been observed that the deposition of carbonaceous soot on the reactor wall is considerably reduced on application of the focusing electric field. Transmission electron microscopy has been used to determine the morphology of the nanotubes. In addition, Raman spectroscopy has helped in distinguishing the graphene-like structures from the disordered carbon networks and helped in analysing the morphology of the tubes. Thermal analysis gave a qualitative estimation of the relative yield of carbon nanotubes within the cathode deposits and their thermal stabilities. The crystalline nature of the samples has been confirmed by x-ray diffraction analysis. The results clearly indicate that the focusing electric field confines the positively charged carbon precursors within the cathode-anode space causing high relative yield and purity and has a distinct effect on controlling the inner diameter of the as-synthesized carbon nanotubes.

In situ optical emission spectroscopic investigations during arc plasma synthesis of iron oxide nanoparticles by thermal plasma - Banerjee, Indrani; Joshi, N. K.; Sahasrabudhe, S. N.; Kulkarni, Naveen V.; Karmakar, Soumen; Pasricha, R.; Ghorui, S.; Tak, Atul K.; Murthy, Shri P. S. S.; Bhoraskar, S. V.; Das, A. K. (IEEE Transactions on Plasma Science, 2006)
Investigations using in situ precursor spectroscopy during the growth of nanoparticles of iron oxide by thermal plasma induced gas phase condensation method have been shown to be useful for correlating the size of nanoparticles with existing plasma parameters. The relative abundance of ionized Fe species inside the plasma plume is seen to directly establish the relation between particle size, arc current, arc length, and ambient pressure of the reacting oxygen gas. The argon plasma from a transferred arc reactor is made to impinge on the anode that is allowed to vaporize and react with oxygen. The spectral line profiles of both Ar and Fe along the plasma column during the synthesis of nanoparticles have been proved to be useful in understanding the growth mechanism. Band intensities of FeO molecular states indicated the inverse relation with particle sizes that have been correlated to the two competitive processes in which energy is released, namely: 1) one involving the radiative transition and 2) the other that of the growth by coagulation. Atomic Boltzmann plots are used for estimating the temperatures of the zones, whereas particle sizes have been inferred using transmission electron microscopic measurements.
Keywords: plasma arc device; plasma-materials processing applications; spectroscopy

Irradiation effects of 12 eV oxygen ions on polyimide and fluorinated ethylene propylene - Majeed, Riyadh M A Abdul; Purohit, V. S.; Bhoraskar, S. V.; Mandale, A. B.; Bhoraskar, Vasant N. (Radiation Effects and Defects in Solids, 2006)
Polyimide (PI) and Fluorinated Ethylene Propylene (FEP) samples (15mm x 15mm x 50 mu m ) were exposed to atomic oxygen ions of average energy similar to 12 eV and flux similar to 5x10(13) ions cm(-2) s(-1) , produced in the Electron Cyclotron Resonance (ECR) plasma. The energy and the flux of the oxygen ions at different positions in the plasma were measured by a retarding field analyzer. The fluence of the oxygen ions was varied from sample to sample in the range of similar to 5x10(16) to 2x10(17) ions cm(-2) by changing the irradiation period. The pre- and the post-irradiated samples were characterized by the weight loss, Scanning Electron Microscopy (SEM), X-ray Photoelectron Spectroscopy (XPS), and Fourier Transform Infrared (FTIR) techniques. The weight of the PI and FEP samples decreased with increasing the ion fluence. However, the erosion yield for the PI is found to be higher, by almost a factor five, when compared with that of FEP. On the surface region of irradiated samples, the concentrations of the carbon, fluorine, and oxygen and their corresponding chemical bonds have changed appreciably. Moreover, blisters and nanoglobules were also observed even at a fluence of similar to 10(17) ions cm(-2) . This oxygen ion fluence is almost two orders of magnitude lower than that of the 5 eV atomic oxygen, which a satellite encounters in the space, at the low Earth orbit, during its mission period of about 7 years.
Keywords: atomic oxygen; ECR plasma; FEP; FTIR; Polyimide; SEM; weight loss; XPS

Nitridation of high speed steel by electron cyclotron resonance plasma - Majeed, Riyadh M A Abdul; Purohit, Vishwas; Bhide, Rajesh; Mandale, A. B.; Bhoraskar, S. V.; Bhoraskar, Vasant N. (Journal of Physics D-Applied Physics, 2006)
Plasma nitridation of high speed M2 steel is studied using a microwave assisted electron cyclotron resonance plasma source. A mixture of hydrogen and nitrogen with a proportion of 7 : 3 was used as the nitriding gas. The density of plasma for this forming gas was measured to be similar to 10(18) m(-3) as estimated by a double probe method. The M2 steel was nitrided at various temperatures of 400, 450, 500 and 550 degrees C under similar reactor conditions. The nitrided layer was characterized by using various analytical techniques which included structural, morphological, chemical and microhardness measurement. The maximum thickness of the nitrided layer was found to be 48 mu m for samples nitrided at 550 degrees C. No layer corresponding to white/compound layer is seen in our analysis. The hardness is seen to increase from similar to 580HV to similar to 1190HV for samples nitrided at 550 degrees C. Electron cyclotron resonance plasma nitridation is observed to be much faster and a cleaner process as compared with the conventional nitriding process.

Preparation of gamma-Fe2O3 nanoparticles using DC thermal arc-plasma route, their characterization and magnetic properties - Banerjee, Indrani; Khollam, Y. B.; Balasubramanian, C.; Pasricha, R.; Bakare, P. P.; Patil, K. R.; Das, A. K.; Bhoraskar, S. V. (Scripta Materialia, 2006)
gamma-Fe2O3 particles were prepared, for the first time, using a direct current thermal arc-plasma route. The powder was characterized using X-ray diffraction, Mossbauer spectroscopy, X-ray photoelectron spectroscopy, chemical analysis, vibrating sample magnetometry C and transmission electron microscopy. The high purity, stoichiometry and spherical morphology of the gamma-Fe2O3 particles (saturation magnetization = 79 emu g(-1) and coercivity = 348 Oe) were confirmed. (c) 2006 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: chemical analysis; DC thermal arc-plasma route; maghemite; Mossbauer spectroscopy; XPS

Mossbauer spectroscopic investigations of nanophase iron oxides synthesized by thermal plasma route - Nagar, Harshada; Kulkarni, Naveen V.; Karmakar, Soumen; Sahoo, B.; Banerjee, Indrani; Chaudhari, P. S.; Pasricha, R.; Das, A. K.; Bhoraskar, S. V.; Date, Sadgopal K.; Keune, W. (Materials Characterization, 2008)
Magnetic nanoparticles of iron oxide were synthesized by transferred arc plasma induced gas phase condensation method. Structural, morphological and magnetic studies of the as synthesized powder were carried out using X-ray diffraction, transmission electron microscopy and Mossbauer spectroscopy. These studies have revealed the simultaneous nucleation and condensation of different magnetic phases with a broad size distribution of the nanoparticles which is peaked at 30-50 nm and ranges from 10 nm to 80 nm. 57 Fe Mossbauer spectra recorded at various temperatures (5 K-300 K) in presence of external magnetic field (at 5 K) have suggested the presence of different phases of iron oxide with sizable amounts of gamma-Fe2O3 and alpha-Fe2O3 in addition to Fe3O4. The relative concentrations of these phases have been obtained by a self consistent spectral area analysis and were found to be 44:22:34 (%). (C) 2007 Elsevier Inc. All rights reserved.
Keywords: iron oxides; Mossbauer spectroscopy; phase analysis; plasma synthesis

Scanning tunneling microscopic and field emission microscopic studies of nanostructured molybdenum film synthesized by electron cyclotron resonance plasma - Purohit, Vishwas S.; Bhise, Ashok B.; Dey, Shirshendu; More, Mahendra A.; Dharmadhikari, C. V.; Joag, Dilip S.; Pasricha, Renu; Bhoraskar, S. V. (Vacuum, 2008)
Cathodic sputtering is demonstrated to be effective in synthesizing thin films of molybdenum nanoparticles. An electron cyclotron resonance plasma reactor has been used as the source. The particle size distribution is found to be controllable by proper choice of the cathodic bias potential. Sizes ranging between 20 and 30 nm deposited at the optimum bias potential are found to exhibit a self assembled structure as observed by scanning tunneling microscopy. Field emission microscopic studies on these films supported on W have exhibited very stable emission current over a period of 3 h. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: ECR plasma; Field emission microscopy; Hollow cathode chemical sputtering; Mo nanoparticles; Scanning tunneling microscopy

Composites of plasma treated poly(etherimide) films with gold nanoparticles and lysine through layer by layer assembly: a ``friendly-rough'' surface for cell adhesion and proliferation for tissue engineering applications - D'Britto, Virginia; Tiwari, S.; Purohit, V.; Wadgaonkar, P. P.; Bhoraskar, S. V.; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2009)
A composite film fabricated by plasma treated poly(etherimide) with subsequent deposition of gold nanoparticles and lysine using layer by layer assembly has been demonstrated to be good for cell attachment and proliferation making it an attractive strategy for tissue engineering applications. As compared to the other methods the decrease in contact angle obtained here does not depend much on the plasma treatment thus affecting the polymer structure minimally. A combination of surface roughness provided by the gold nanoparticles and the presence of amine groups of lysine is hypothesized to be the reason for the features observed.

Influence of filler size and morphology in controlling the thermal emissivity of aluminium/polymer composites for space applications - Babrekar, Harshada A.; Kulkarni, Naveen V.; Jog, Jyoti Prakash; Mathe, Vikas L.; Bhoraskar, S. V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
The paper has addressed the problem of controlling the thermal emissivities from metal/polymer composites prepared by solution method. Aluminium is used as a filler and polystyrene as a polymer-matrix. Aluminium particles, with micrometer and nanometer dimensions having different morphologies, were employed. The values of emissivities were reduced when the coarse grains and flakes of aluminium were used as fillers, whereas, no significant change was observed when nano-aluminium was used in the composite. Dielectric dispersion for the composites was measured and the results are analysed in view of Fresnel relation. The differences in the values of dielectric constants, between the experimentally measured and those which can be predicted theoretically, are thought to arise from the interfacial polarization. (C) 2009 Elsevier B.V. All rights reserved.
Conference on Specialty Advanced Materials and Polymers for Aerospace and Defense and Applications (SAMPADA-2008), Mat Res Soc Singapore, Singapore, SINGAPORE, JUL 03-08, 2005
Keywords: Camouflaging; Composite; dielectric constant; Infra-red; Thermal emissivity

Study of the effect of plasma-striking atmosphere on Fe-oxidation in thermal dc arc-plasma processing - Banerjee, Indrani; Khollam, Y. B.; Mahapatra, S. K.; Das, A. K.; Bhoraskar, S. V. (Journal of Vacuum Science & Technology A, 2010)
The effect of plasma-striking atmosphere: air and air+Ar-gas on the crystallization of Fe-oxide phases was studied using dc thermal arc-plasma processing route. The powders were characterized by x-ray diffraction, vibrating sample magnetometry, transmission electron microscopy, and Mossbauer spectroscopy techniques. At room temperature and O(2) rich atmosphere, arc-evaporated Fe(2+) ions oxidize into either gamma-Fe(2)O(3) or Fe(3)O(4) depending upon the combining ratio of Fe with molecular O(2). Fe/O ratio could be adjusted using proper flow rate of Ar gas to crystallize the pure gamma-Fe(2)O(3). (C) 2010 American Vacuum Society. [DOI: 10.1116/1.3504597]

Field emission studies of silver nanoparticles synthesized by electron cyclotron resonance plasma - Purohit, Vishwas; Mazumder, Baishakhi; Bhise, Ashok B.; Poddar, Pankaj; Joag, Dilip S.; Bhoraskar, S. V. (Applied Surface Science, 2011)
Field emission has been studied for silver nanoparticles (25-200 nm), deposited within a cylindrical silver target in an electron cyclotron resonance (ECR) plasma. Particle size distribution was controlled by optimum biasing voltages between the chamber and the target. Presence of non-oxidized silver was confirmed from the X-Ray diffraction analysis; however, thin protective layer of oxide was identified from the selective area electron diffraction pattern obtained with transmission electron microscopy. The silver nanoparticles were seen to exhibit hilly pointed like structures when viewed under the atomic force microscopy (AFM). The emissive properties of these particles were investigated by field emission microscopy. It is found that this technique of deposition is ideal for formation of nanoparticles films on different substrate geometries with size controllability as well as its application to emission devices. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cold plasma; field emission; Nanoparticles; thin film

Low thermal emissive surface properties of ZnO/polyimide composites prepared by pulsed laser deposition - Babrekar, Harshada A.; Jejurikar, S. M.; Jog, Jyoti Prakash; Adhi, K. P.; Bhoraskar, S. V. (Applied Surface Science, 2011)
We report the low thermal-emissive surface properties of composites of ZnO-polyimide. The composites were synthesized by depositing ZnO on polyimide surface by pulsed laser deposition technique. ZnO target was ablated at different incident energy densities and the substrate (polyimide) was held at elevated temperature. This facilitated the c-axis oriented growth of ZnO, which was inferred from the X-ray diffraction analysis. The composites consisted of multilayers having different electrical resistivities. The values of which are also estimated from Hagen-Rubens relation. The reduced infrared emissivities of the composite films, as compared to polyimide, were correlated to the increased carrier concentration and reduced surface resistivity estimated from the Hall measurements. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: pulsed laser deposition; Thermal emissivity; Thin films; Zinc oxide

Magnetic properties of thermal plasma synthesized nanocrystalline nickel ferrite (NiFe2O4) - Nawale, Ashok B.; Kanhe, Nilesh S.; Patil, K. R.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Journal of Alloys and Compounds, 2011)
A rapid synthesis method is reported for magnetic nanoparticles of nickel ferrite involving thermal plasma assisted vapor phase condensation process. The as-synthesized samples were characterized by X-ray Diffraction, Transmission Electron Microscopy, Vibrating Sample Magnetometer and X-ray Photoelectron Spectroscopy techniques. The average particle size was determined from the TEM micrographs and found to be around 30 nm. The effects of reactor parameters on the magnetic and structural properties have been evaluated, to find the optimized parameters so as to achieve the highest values of saturation magnetization and coercivity. Reasonably high saturation magnetization (48 emu/g) has been assigned to the high degree of crystallinity, achieved on account of high temperature during the growth, and the cation redistribution. The high value of coercivity (1150e) is explained on the basis of possible lattice defects arising from the cation redistribution. Detailed analysis of cation distribution using the XRD line intensity data leads to the conclusion that these samples are iron deficit and nickel rich. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: crystal structure; Magnetic measurements; Magnetization; Nanostructured materials; TEM

Silver nanoparticle studded porous polyethylene scaffolds: bacteria struggle to grow on them while mammalian cells thrive - D'Britto, Virginia; Kapse, Harsha; Babrekar, Harshada A.; Prabhune, Asmita; Bhoraskar, S. V.; Premnath, V.; Bhagavatula L. V. Prasad (Nanoscale, 2011)
Silver nanoparticle studded scaffolds were prepared by exploiting the Ag+ ion reducing activity of sophorolipids-a class of `glycolipids' that cap the ensuing nanoparticles as well. To achieve this, the porous polyethylene scaffolds are subjected to N-2+H-2 plasma treatment, in the first step. Subsequently the sophorolipids are covalently attached to the amine groups on the polymer surface through simple amide chemistry to yield sophorolipid grafted polymer scaffolds. These are then exposed to Ag+ ions under appropriate conditions leading to the formation of silver nanoparticles immobilized on the polymer scaffolds. It has been found that while bacteria do not survive on these silver studded scaffolds, CHO-K1 cells thrive on them making them good candidates for tissue engineering and bio-implant applications.

Magnetic properties of nanocrystalline CoFe2O4 synthesized by thermal plasma in large scale - Nawale, A. B.; Kanhe, Nilesh S.; Patil, K. R.; Reddy, V. R.; Gupta, A.; Kale, B. B.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Materials Chemistry and Physics, 2012)
The paper reports the large scale synthesis of nanoparticles of CoFe2O4 using thermal plasma reactor by gas phase condensation method. The yield of formation was found to be around 15 g h(-1). The magnetic properties of CoFe2O4, synthesized at different reactor powers, were investigated in view of studying the effect of operating parameters of plasma reactor on the structural reorganization leading to the different cation distribution. The values of saturation magnetization, coercivity and remanent magnetization were found to be influenced by input power in thermal plasma. Although the increase in saturation magnetization was marginal (61 emu g(-1) to 70 emu g(-1)) with increasing plasma power; a significant increase in the coercivity (552 Oe to 849 Oe) and remanent magnetization (16 emu g(-1) to 26 emu g(-1)) were also noticed. The Mossbauer spectra showed mixed spinel structure and canted spin order for the as synthesized nanoparticles. The detailed analysis of cation distribution using the Mossbauer spectroscopy and X-ray photoelectron spectroscopy leads to the conclusion that the sample synthesized at an optimized power shows the different site selective states. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic materials; magnetic properties; Mossbauer spectroscopy; Nanostructures

Swift heavy ion induced formation of Al/polymer composite layer for low thermal emissivity in the IR range - Babrekar, Harshada A.; Jog, Jyoti Prakash; Mathe, Vikas L.; Avasthi, D. K.; Ojha, S.; Bhoraskar, S. V. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2012)
Composites of polymers with aluminium were formed by swift high energy ions of 150 MeV, which are used as low thermal emissivity materials for infrared wavelengths between 8-14 mu m. Emissivity and dielectric constants were studied for these structures. A semi-empirical model has been established to obtain the relation between emissivity and dielectric constant. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: composites; dielectric constant; Swift heavy ion; Thermal emissivity

Understanding the growth of micro and nano-crystalline AlN by thermal plasma process - Kanhe, Nilesh S.; Nawale, Ashok B.; Gawade, Rupesh L.; Puranik, Vedavati G.; Bhoraskar, S. V.; Das, Asoka K.; Mathe, Vikas L. (Journal of Crystal Growth, 2012)
We report the studies related to the growth of crystalline AlN in a DC thermal plasma reactor, operated by a transferred arc plasma torch. The reactor is capable of producing the nanoparticles of Al and AlN depending on the composition of the reacting gas. Al and AlN micro crystals are formed at the anode placed on the graphite and nano crystalline Al and AlN gets deposited on the inner surface of the plasma reactor. X-ray diffraction, Raman spectroscopy analysis, single crystal X-ray diffraction and TGA-DTA techniques are used to infer the purity of post process crystals as a hexagonal AlN. The average particle size using SEM was found to be around 30 mu m. The morphology of nanoparticles of Al and AlN, nucleated by gas phase condensation in a homogeneous medium were studied by transmission electron microscopy analysis. The particle ranged in size between 15 and 80 nm in diameter. The possible growth mechanism of crystalline AlN at the anode has been explained on the basis of non-equilibrium processes in the core of the plasma and steep temperature gradient near its periphery. The gas phase species of AlN and various constituent were computed using Murphy code based on minimization of free energy. The process provides 50% yield of microcrystalline AlN and remaining of Al at anode and that of nanocrystalline h-AlN and c-Al collected from the walls of the chamber is about 33% and 67%, respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Crystal morphology; Growth from high temperature solutions; Nitride; Semiconducting aluminum compound

Electrokinetic properties of PMAA functionalized NiFe2O4 nanoparticles synthesized by thermal plasma route - Bhosale, Shivaji V.; Mhaske, Pravin; Kanhe, N.; Navale, A. B.; Bhoraskar, S. V.; Mathe, V. L.; Bhatt, S. K. (Solid State Physics: Proceedings of the 58th Dae Solid State Physics Symposium 2013, PTS A & B, 2014)
The magnetic nickel ferrite (NiFe2O4) nanoparticles with an average size of 30nm were synthesised by Transferred arc DC Thermal Plasma route. The synthesized nickel ferrite nanoparticles were characterized by TEM and FTIR techniques. The synthesized nickel ferrite nanoparticles were further functionalized with PMAA (polymethacrylic acid) by self emulsion polymerization method and subsequently were characterized by FTIR and Zeta Analyzer. The variation of zeta potential with pH was systematically studied for both PMAA functionalized (PNFO) and uncoated nickel ferrite nanoparticles (NFO). The IEP (isoelectric points) for PNFO and NFO was determined from the graph of zeta potential vs pH. It was observed that the IEP for NFO was at 7.20 and for PNFO it was 2.52. The decrease in IEP of PNFO was attributed to the COOH functional group of PMAA.
Keywords: IEP; NiFe2O4; PMAA; Thermal plasma; Zeta potential

Micro-structural analysis of NiFe2O4 nanoparticles synthesized by thermal plasma route and its suitability for BSA adsorption - Bhosale, Shivaji V.; Kanhe, Nilesh S.; Bhoraskar, S. V.; Bhat, Suresh K.; Bulakhe, Ravindra N.; Shim, Jae-Jin; Mathe, Vikas L. (Journal of Materials Science-Materials in Medicine, 2015)
The paper presents the experimental studies pertaining to the adsorption of bovine serum albumin (BSA) on the nanoparticles of nickel ferrite (NiFe2O4) with a view of correlating the adsorption properties to their microstructure and zeta potentials. Physical properties of two kinds of nickel ferrites, one synthesized by thermal plasma route and the other by chemical co-precipitation method, are compared. Maximum adsorption (231.57 lg/mg) of BSA onto nickel ferrite nanoparticles, at body temperature (37 degrees C) was observed at pH-value of 5.58 for the thermal plasma synthesized particles showing its higher adsorption capacity than those synthesized by wet chemical means (178.71 mu g/mg). Under the same physical conditions the value of zeta potential, obtained for the former, was higher than that of the latter over a wide range of pH values (3.64-9.66). This is attributed to the differences in the specific surface energies of the two kinds of nanoparticles arising from the degree of crystallinity. The paper presents the experimental evidence for the single crystalline nature of the individual nanoparticles, with mean size of 32 nm, for the thermal plasma synthesized particles as evidenced from the high resolution transmission electron microscopy and electron diffraction analysis. The measurements also reveal the poor crystalline morphology in the chemically prepared particles (mean size of 28 nm) although the X-ray diffraction patterns are not much different. The atomic force microscopy images confirm that the surfaces of plasma synthesized nanoparticles possesses higher surface roughness than that of chemically synthesized one. Presence of adsorbed protein was confirmed by vibrational spectroscopy. The Langmuir adsorption model is found to fit into the experimental data better than the Freundlich adsorption model.

Surface chemical bonds, surface-enhanced Raman scattering, and dielectric constant of SiO2 nanospheres in-situ decorated with Ag-nanoparticles by electron-irradiation - Phatangare, A. B.; Dhole, S. D.; Dahiwale, S. S.; Mathe, V. L.; Bhoraskar, S. V.; Late, Dattatray J.; Bhoraskar, V. N. (Journal of Applied Physics, 2016)
Nanostructures of dielectric materials decorated with metal nanoparticles are of great scientific interest; however, the involved synthesis methods are complicated and require multistep chemical processing, including functionalization of the dielectric surfaces. In the present work, without chemical processes, silver nanoparticles of average sizes in the range of 11 to 15 nm were in-situ synthesized and decorated on SiO2 nanospheres in a single step process by irradiating a solution (AgNO3-polyvinylpyrrolidone (PVP)-SiO2 nanospheres) with 6 MeV electrons at 1.5 x 10(15) e(-)/cm(2), 3.0 x 10(15) e(-)/cm(2), and 4.5 x 10(15) e(-)/cm(2) fluences. The electron irradiated solutions were characterized with different surface and other techniques. The results revealed that the SiO2 nanospheres were uniformly decorated with Ag nanoparticles, and the prominent chemical bonds involved were Ag-O, Si-O-Ag, and Si-Ag. Moreover, the sizes and the decoration density of Ag nanoparticles could be tailored by varying electron fluence. The Surface-enhanced Raman scattering (SERS) of 4-aminothiophenol (4-ATP) solutions was studied using substrates in the form of thin coatings of the solutions of Ag-decorated SiO2 nanospheres. The appearance of the characteristic SERS peaks of both 4-ATP and 4, 4'-dimercaptoazobenzene (4, 4'-DMAB) in Raman spectra confirmed the conversion of a fraction of 4-ATP into 4, 4'-DMAB in the presence of Ag nanoparticles. Composites in the form of thin films were synthesized from the mixture solutions of PVP and Ag-decorated SiO2 nanospheres. The dielectric constant of each thin film was higher as compared to polymers, and could be tailored by varying electron fluence used for decorating Ag nanoparticles. Published by AIP Publishing.